Penggunaan Katalis NaOH dalam Proses Transesterifikasi Minyak Kemiri menjadi Biodiesel - Mulana, Farid (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2011)
Research on biodiesel production from hazelnut oil by transesterification process using NaOH catalyst was one of the efforts for renewable energy research. The purpose of this study was to determine the effect of NaOH catalyst and the ratio of hazelnut oil to methanol on the production of biodiesel via transesterification process. The transesterification process was carried out in a stirred reactor equipped by a condenser with speed of 200 rpm, temperature of 60C and the operating time of 90 minutes. The results indicated that biodiesel could be produced from hazelnut oil through transesterification process with the highest yield of 81.7% that was obtained on the use of 2% wt. of NaOH catalyst and the mole ratio of oil to methanol of 1:9. Viscosity, density, and acid number of biodiesel obtained in this study met the Indonesia National Standard for biodiesel as SNI 04-7182-2006, therefore hazelnut oil produced biodiesel could potentially be an alternative diesel fuel.Keywords: hazelnut oil, biodiesel, transesterification, NaOH catalyst